2022
DOI: 10.3389/fnbeh.2022.836343
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Inter-Individual Variability and Vulnerability: The Role of Dopamine

Abstract: Individuals differ in their traits and preferences, which shape their interactions, their prospects for survival and their susceptibility to diseases. These correlations are well documented, yet the neurophysiological mechanisms underlying the emergence of distinct personalities and their relation to vulnerability to diseases are poorly understood. Social ties, in particular, are thought to be major modulators of personality traits and psychiatric vulnerability, yet the majority of neuroscience studies are per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 170 publications
(240 reference statements)
0
10
0
Order By: Relevance
“…It acts as a modulator, influencing the salience and motivational value assigned to stimuli and guiding the selection of appropriate actions in response to environmental cues. This central position of the dopaminergic system, shared by numerous brain regions, allows us to conceptualize a neural basis for the notion of individuality 20 . Thus, in this sense, our results suggest that a dynamic feedback loop exists between environmental encounters and the dopaminergic system which continually defines animal traits and adaptability to future challenges.…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a modulator, influencing the salience and motivational value assigned to stimuli and guiding the selection of appropriate actions in response to environmental cues. This central position of the dopaminergic system, shared by numerous brain regions, allows us to conceptualize a neural basis for the notion of individuality 20 . Thus, in this sense, our results suggest that a dynamic feedback loop exists between environmental encounters and the dopaminergic system which continually defines animal traits and adaptability to future challenges.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in schizophrenia patients, interindividual variability has been observed across cognitive tests, giving rise to cognitive heterogeneity as a clinical characteristic of the disorder [80]. A rodent study demonstrated inter-individual variability in social testing environments, attributed to the differential expression of dopamine neurons in response to environmental stimuli [81].…”
Section: Effect Of Lps On Behaviour Of Offspringmentioning
confidence: 99%
“…The examples of variation in ASM responsiveness described above are representative of observations in an increasing number of laboratory studies in neuroscience and other disciplines that have found wide variability in outcomes ( Good and Hardin, 2012 ; Bernard, 2023 ; Marder, 2023 ). Laboratory experiments in experimental psychiatry are particularly prone to this phenomenon ( Pitychoutis et al, 2011 ; Armario and Nadal, 2013 ; Aiello et al, 2015 ; Dellu-Hagedorn et al, 2018 ; Neyazi et al, 2018 ; van der Goot et al, 2021 ; Faure et al, 2022 ). As in our experience, it has often been noted that the common practice of averaging data can lead to erroneous conclusions.…”
Section: Averaging Data Can Lead To Misinterpretations In Neurosciencementioning
confidence: 99%
“…Even before inducing psychopathology or neurological disease, rodents of the same strain, sex, and age may differ in their intrinsic behavioral characteristics, which may affect the subsequent development of experimentally induced pathologies ( Armario and Nadal, 2013 ; Theilmann et al, 2016 ; Faure et al, 2022 ; Strekalova et al, 2022 ; Löscher and White, 2023 ). For instance, inter-individual differences in baseline anxiety-like behavior (ALB) in Wistar rats affected subsequent amygdala kindling in that only rats with increased baseline ALB before kindling exhibited a lasting increase in ALB after kindling ( Adamec and Shallow, 2000 ).…”
Section: Variation In Disease Susceptibilitymentioning
confidence: 99%